2019
DOI: 10.3390/ma12111754
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Adhesion of Silicate Glass–Ceramic Coatings onto Alumina for Biomedical Applications

Abstract: Deposition of bioactive glass or ceramic coatings on the outer surface of joint prostheses is a valuable strategy to improve the osteointegration of implants and is typically produced using biocompatible but non-bioactive materials. Quantifying the coating–implant adhesion in terms of bonding strength and toughness is still a challenge to biomaterials scientists. In this work, wollastonite (CaSiO3)-containing glass–ceramic coatings were manufactured on alumina tiles by sinter-crystallization of SiO2–CaO–Na2O–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…21,49 However, in our process, the formation of chemical bonds like Si-O-Si to connect the UGF and Ti plate is formed and gets high bonding strength larger than ~900 mJ/m 2 by just storing the bonded sample in the ambient atmosphere at room temperature. Previous studies 50,51 have shown that a bioactive glass-ceramics coating on a alumina substrate with a bonding strength of ~800 mJ/m 2 had a tensile strength of ~22 MPa. Thus, a tensile strength higher than 22 MPa may have been obtained between the UGF and Ti plate in 9h stored sample in our study, which exceeds the requirement of the international standard for bioactive hydroxyapatite coating implants (15 MPa, ISO 13 779-2).…”
Section: Discussionmentioning
confidence: 99%
“…21,49 However, in our process, the formation of chemical bonds like Si-O-Si to connect the UGF and Ti plate is formed and gets high bonding strength larger than ~900 mJ/m 2 by just storing the bonded sample in the ambient atmosphere at room temperature. Previous studies 50,51 have shown that a bioactive glass-ceramics coating on a alumina substrate with a bonding strength of ~800 mJ/m 2 had a tensile strength of ~22 MPa. Thus, a tensile strength higher than 22 MPa may have been obtained between the UGF and Ti plate in 9h stored sample in our study, which exceeds the requirement of the international standard for bioactive hydroxyapatite coating implants (15 MPa, ISO 13 779-2).…”
Section: Discussionmentioning
confidence: 99%
“…The development of structural defects and microcracks in thicker coatings weakens the interfacial bond. (17) In the same context, Baino (12) concluded that a silica based glass coating thickness below 250 µm was considered convenient for the biomedical purposes. However, Monsalve et al (18) found that decreasing the BAG coating thickness below 80 µm enhanced the adhesive strength of the coating to the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the signi cant developments of adhesive and cementation agents, there have been advances in the bonding technology for glass-ceramic [7,8,9]. And using glass-ceramic onlays in the restoration of posterior tooth defect is becoming more popular [10,11].…”
mentioning
confidence: 99%